Prostate cancer radiotherapy [Polish version: Radioterapia raka gruczołu krokowego p... 323] - Kulik, Anna; Dąbkowski, Mateusz (Contemporary Oncology/Współczesna Onkologia, 2011)
Prostate cancer is one of the most commonly diagnosed malignancies in males. Surgery and radiotherapy are primary methods of curative treatment in patients with this diagnosis. Development of technology and long-term clinical experience enable optimisation of radiotherapy for all clinical stages of the disease. The purpose of this paper is to present general principles of treatment selection and conduct in prostate cancer patients to doctors who are not specialists in medical oncology or radiotherapy. If teleradiotherapy (external beam radiotherapy – EBRT) is used, ionising radiation is generated outside the patient’s body, usually with the use of linear accelerators. Brachytherapy is the second basic radiotherapy method, where the source of ionising radiation is introduced into the tumour or placed in its direct neighbourhood. The results of numerous clinical studies indicate that radiotherapy offers a possibility to cure patients in various clinical stages of the disease with a continuously decreasing rate of serious radiotherapy sequelae.